Programming 32-bit microcontrollers in C exploring the PIC32 - Di Jasio, Lucio (Embedded technology series, 2008)
Embedded control designers have been constantly asking for more performance, more memory and more power to complete ever more advanced applications. Microchip latest and greatest 32-bit architecture, the PIC32, has been designed specifically to fulfill those demands offering an unprecedented level of performance by merging seamlessly the industry acclaimed MIPS 32-bit core with the trusted peripheral and feature set, common to all previous generations of PIC microcontrollers, that has made Microchip a world leader in embedded control. The result is an immediate sensation of familiarity and ease of use for all previous PIC microcontroller users and a refreshing sensation of power and friendliness for all those approaching the 32-bit world for the first time.